The role of heat treatments on wear behaviour of 316L stainless steel produced by additive manufacturing - Ozer, Gokhan; Kisasoz, Alptekin (ELSEVIER, 2022)
In this study, 316L stainless steel (SS) samples were produced using Direct Laser Metal Sintering (DMLS) method with standard parameters. Specimens were heat-treated at 650, 950, and 1150 degrees C for 2 h following the DMLS process. Effects of the heat treatments on the properties of DMLS parts were examined by microstructure, hardness, and wear tests. Microstructural properties were investigated by scanning electron microscopy (SEM), X-ray diffraction (XRD), and energy-dispersive X-ray (EDX) analysis. Hardness changes were determined by the Vickers hardness (HV) method. The results showed that the as-built microstructure of DMLS/316L SS deteriorated with the increase in heat treatment temperature. Moreover, heat treatment processes caused a decrease in hardness and wear resistance.
Keywords: Dry sliding wear; Microstructure; Austenitic stainless steel; Direct Metal Laser Sintering (DMLS); TRIBOLOGICAL PERFORMANCE; NANOCOMPOSITES; EVOLUTION; Materials Science; Physics